Zero energy potential of PV direct-driven air conditioners coupled with phase change materials and load flexibility. (November 2022) - Li, Sihui; Peng, Jinqing; Li, Houpei; Zou, Bin; Song, Jiaming; Ma, Tao; Ji, Jie
Abstract: Without any assistance, the energy matching between air conditioner load demand and PV generation of PV direct driven Air Conditioners (PVACs) is inflexible. Phase Change Materials (PCMs) and building load flexibility can improve the real-time Zero Energy Probability (ZEP). In this paper, a coupling system consisting of PVACs, PCMs, and load flexibility was proposed for an office building. Sensitive analysis were conducted for different PCMs coupled with PVACs and load flexibility to improve the real-time ZEP with considering the PV capacity Factors (PVF), PCM type, and PCM thickness. According to the influence on the ZEP, the key parameters of the coupling system were ranked as follows: PVF > PCM melting temperature > PCM thickness. PCMs can reduce the PVF by 26.67% and assist the system achieving a 90% real-time ZEP in summer. The recommended PVF for the Hot-summer and Warm-winter and the Hot-summer and Cold-winter zone are 1.3 and 1.0, respectively, while the optimized PCM melting temperature are 27 °C and 26 °C, respectively. In summary, a complete evaluation method, a universal design route and different optimization schemes for PVACs coupled with PCMs and load flexibility were proposed in this paper, and it is conducive to the improvement of the real-time ZEP.